Evaluation of the Performance Degradation of Hybrid Steel-Polypropylene Fiber Reinforced Concrete under Freezing-Thawing Conditions. (28th December 2020) - Luo, Daming; Wang, Yan; Niu, Ditao
Abstract : The reasonable inclusion of hybrid fibers can leverage the advantages of each kind of fiber and enhance the frost resistance and flexural toughness of concrete. Previous studies on hybrid steel-polypropylene fiber reinforced concrete (HSPFRC) focused primarily on its mechanics instead of its frost resistance. In this work, the compressive strength, splitting tensile strength, mass loss rate, relative dynamic elastic modulus (RDEM), and flexural toughness of HSPFRC after freezing-thawing (F-T) are studied, and the relative importance of each factor affecting the frost resistance of HSPFRC is quantified by using fuzzy rough set theory. The results show that the inclusion of hybrid fibers has a noticeable effect on the frost resistance of HSPFRC after hundreds of F-T cycles and that the effect on the splitting tensile strength is greater than that on the compressive strength. After 500 F-T cycles, as the steel fiber (SF) content increases, the compressive strength and splitting tensile strength increase by factors of approximately 5 and 4, respectively, the flexural toughness is strengthened, and the mass loss rate is reduced by more than 90%. The addition of polypropylene fibers (PFs) has a relatively small effect on the strength of HSPFRC but reduces the mass loss of HSPFRC by almost 80%. However, the suitability of the RDEM for evaluating the frost resistance of HSPFRC remains uncertain. Quantified by fuzzy rough set theory, the weights of the factors affecting the frost resistance of HSPFRC are 0.50 (number of F-T cycles) > 0.35 (SF content) > 0.15 (PF content), verifying the experimental results.